A general strategy for the evolution of bond-forming enzymes using yeast display - Chen, Irwin; Dorr, Brent M.; Liu, David R. (Proceedings of the National Academy of Sciences - PNAS, 2011)
The ability to routinely generate efficient protein catalysts of bond-forming reactions chosen by researchers, rather than nature, is a long-standing goal of the molecular life sciences. Here, we describe a directed evolution strategy for enzymes that catalyze, in principle, any bond-forming reaction. The system integrates yeast display, enzyme-mediated bioconjugation, and fluorescence-activated cell sorting to isolate cells expressing proteins that catalyze the coupling of two substrates chosen by the researcher. We validated the system using model screens for Staphylococcus aureus sortase A—catalyzed transpeptidation activity, resulting in enrichment factors of 6,000-fold after a single round of screening. We applied the system to evolve sortase A for improved catalytic activity. After eight rounds of screening, we isolated variants of sortase A with up to a 140-fold increase in LPETG-coupling activity compared with the starting wild-type enzyme. An evolved sortase variant enabled much more efficient labeling of LPETG-tagged human CD154 expressed on the surface of HeLa cells compared with wild-type sortase. Because the method developed here does not rely on any particular screenable or selectable property of the substrates or product, it represents a powerful alternative to existing enzyme evolution methods.